2014
DOI: 10.1182/blood.v124.21.3269.3269
|View full text |Cite
|
Sign up to set email alerts
|

Hypoplastic MDS Is a Distinct Clinico-Pathological Entity with Somatic Mutations Frequent in Patients with Prior Aplastic Anaemia with Favorable Clinical Outcome

Abstract: Introduction: Hypocellular myelodysplastic syndrome (hMDS) is characterized by decreased marrow cellularity, and is often difficult to distinguish from aplastic anemia (AA) based on standard morphological criteria. It represents around 10-15% of patients diagnosed with MDS, but is not currently considered a separate entity by WHO. Hypocellularity is defined as bone marrow cellularity of less than 30% in patients younger than 70 years or less than 20% in those older than 70 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Patients with hMDS eventually progress to AML at a five-year rate of around 10–40%, somewhat in-between AA and normo/hypercellular MDS [ 6 , 11 , 148 ]. Such an event has been correlated to genetic features so that hMDS patients carrying poorer-risk cytogenetic (del7/7q, complex karyotype) and molecular lesions (spliceosome, cohesin, DNA methylation, TP53) show a higher incidence of leukemic transformation [ 149 , 150 ]. The risk also appears age-related, consistently with an age-dependent distribution of somatic mutations, as described in healthy subjects with age-related clonal hematopoiesis (ARCH) [ 151 ] and as a result of genomic instability.…”
Section: Clonal Evolutionmentioning
confidence: 99%
“…Patients with hMDS eventually progress to AML at a five-year rate of around 10–40%, somewhat in-between AA and normo/hypercellular MDS [ 6 , 11 , 148 ]. Such an event has been correlated to genetic features so that hMDS patients carrying poorer-risk cytogenetic (del7/7q, complex karyotype) and molecular lesions (spliceosome, cohesin, DNA methylation, TP53) show a higher incidence of leukemic transformation [ 149 , 150 ]. The risk also appears age-related, consistently with an age-dependent distribution of somatic mutations, as described in healthy subjects with age-related clonal hematopoiesis (ARCH) [ 151 ] and as a result of genomic instability.…”
Section: Clonal Evolutionmentioning
confidence: 99%
“…Although AA is considered to be a nonmalignant disease with potential cure using IST or alloSCT, it can be complicated by the develop- and is characterized by bone marrow cellularity <30% in patients aged <70 years or <20% cellularity in those older than age 70 years. 93 The impossibility of morphologically distinguishing AA from hMDS has led many experts to identify this phenomenon as an overlap syndrome. A retrospective study of hMDS patients revealed that 62% of patients had normal cytogenetics and only 21% had mutations in either ASXL1, DNMT3A, or BCOR; the overwhelming majority of hMDS patients with a somatic mutation had a prior history of AA.…”
Section: E Viden Ce In Clonal E Voluti On and Que S Tions From Clonmentioning
confidence: 99%
“…A retrospective study of hMDS patients revealed that 62% of patients had normal cytogenetics and only 21% had mutations in either ASXL1, DNMT3A, or BCOR; the overwhelming majority of hMDS patients with a somatic mutation had a prior history of AA. 93 Because of these inconsistencies, the presence of CH does not aid in the distinction between AA and hMDS. In fact, the identification of several cytogenetic aberrations (for instance, monosomy 7, which is identified in up to 13% of AA cases at diagnosis) by conventional karyotyping is diagnostic of MDS even in the absence of morphologic dysplasia as per the World Health Organization (WHO) classification of myeloid neoplasms.…”
Section: E Viden Ce In Clonal E Voluti On and Que S Tions From Clonmentioning
confidence: 99%
See 2 more Smart Citations